Developing a hospital accreditation model: a Delphi study - Ali Mohammad Mosadeghrad; Fatemeh Ghazanfari (BMC, 2021)
Abstract Background Hospital accreditation (HA) is an external evaluation of a hospital's structures, processes and results by an independent professional accreditation body using pre-established optimum standards. The Iranian hospital accreditation system faces several challenges. The overall aim of this study was to develop a model for Iran national hospital accreditation program. Methods This research uses the modified Delphi technique to develop and verify a model of hospital accreditation. The first draft of the HA model was introduced through a critical review of 20 pioneer accreditation models and semi-structured interviews with 151 key informants from Public, private, semi-public, charity and military hospitals in Iran. Three rounds of Delphi were conducted with 28 experts of hospital accreditation to verify the proposed model. Panel members were selected from authors of research articles and key speakers in the area of hospital accreditation, senior managers of the country's health system, university professors in the fields of health policy and management across the country. Results A comprehensive model for hospital accreditation was introduced and verified in this study. The HA model has ten constructs of which seven are enablers ("Management and leadership", "Planning", "Education and Research", "employee management", "patient management", "resource management", and "process management") and three are the results ("employee results", "patient and society results" and "hospital results"). These constructs were further broken into 43 sub-constructs. The enablers and results scored 65 and 35% of the model's total scores respectively. Then, about 150 accreditation standards were written and verified. Conclusions A comprehensive hospital accreditation model was developed and verified. Proper attention to structures, processes and outcomes and systemic thinking during the development of the model is one of the advantages of the hospital accreditation model developed in this study. Hospital accreditation bodies can use this model to develop or revise their hospital accreditation models.